Environmental changes impact the human body - Abdul Rahim, Roslina (2024)
Climate change is characterized by long-term alterations in temperature and rainfall patterns within a region. Its effects include the elevation of sea levels, the melting of ice in Greenland, the Arctic, and Antarctic poles, the reduction of glaciers on mountains, altering in the timing of flower and plant blooming, shifts in animal populations, and significant health consequences. Moreover, it has heightened the occurrence and severity of extreme weather events, including heatwaves, droughts, storms, hurricanes, and floods.